O FUTURO DA LITIGÂNCIA CLIMÁTICA NO BRASIL: UMA ANÁLISE A PARTIR DO DESCUMPRIMENTO DE ACORDOS INTERNACIONAIS E AGENDA 2030 (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
Climate litigation has shown a significant numerical growth in recent years, along with the number of countries where lawsuits have been filed. In Brazil, the number of lawsuits is still considered incipient, although, paradoxically, the country presents a regulatory framework of collective protection considered consolidated, a notorious governmental noncompliance with the Paris Agreement and proven setbacks in the implementation of the goals of SDG 13 of Agenda 2030, whose goal is to implement urgent measures to combat climate change and its impacts.  In this scenario, the article aims to analyze climate litigation at the global and national levels, the instruments of collective judicial protection aimed at climate litigation in Brazil, and the government's attitude towards the international agreements to which it is a signatory, especially the 2030 Agenda. The method used to analyze this study is analytical, supported by theoretical research based on bibliographic and doctrinal surveys and research on climate litigation. The article concludes that the scenario of poor government management, together with the frustration of the results of the monitoring of the implementation of the commitments made by the country at the global level, accredits the national climate litigation to join the list of world references, on the level of countries with the highest number of lawsuits, reflecting an urgency in face of the impacts to the planet if the measures already taken are not observed and fulfilled.